2010
DOI: 10.1021/ma102043d
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effects on Cross-Linking within Electrostatic Layer-by-Layer Assemblies Containing Poly(allylamine hydrochloride) and Poly(acrylic acid)

Abstract: Thermal cross-linking is widely used to impart stability or improved mechanical properties to layer-by-layer (LbL) assemblies. However, the kinetics of thermal cross-linking within LbL films is not well understood. Furthermore, because LbL films are generally ultrathin (<100 nm), the influence of confinement on cross-linking kinetics is potentially substantial. Using temperature-controlled ellipsometry, differential scanning calorimetry, and thermal gravimetric analysis, we are able to accurately track amide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 58 publications
6
39
0
Order By: Relevance
“…They prepared ultra-thin PS films and their ellipsometric results of the change in thickness vs. temperature showed two linear regions of thermal expansivity, which they related to the polymer glass and melt temperatures. They report that the point that divides two regions was associated to the Tg of the polymer [69]. Relying on these results and the behavior registered over the increase and expansion of the thickness of the polymeric multilayers formed by the layer-by-layer technique, we have attributed this behavior to the Tg of the multilayers.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…They prepared ultra-thin PS films and their ellipsometric results of the change in thickness vs. temperature showed two linear regions of thermal expansivity, which they related to the polymer glass and melt temperatures. They report that the point that divides two regions was associated to the Tg of the polymer [69]. Relying on these results and the behavior registered over the increase and expansion of the thickness of the polymeric multilayers formed by the layer-by-layer technique, we have attributed this behavior to the Tg of the multilayers.…”
Section: Resultsmentioning
confidence: 57%
“…Lutkenhaus and her group studied the thermal properties of LbL films of poly(diallyldimethylammonium chloride)/poly(styrene sulfonate) (PDAC/PSS) [69]. They found that different thermal transitions of the multilayers can be observed depending on the properties of the solution used to prepare the multilayers; for example, the ionic force or whether they are hydrated or not.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, some PEMs can exhibit limited stability upon changes in pH, ionic strength, and temperature (or upon exposure to other ''harsh'' environments) that can disrupt the weak ionic interactions that stitch these materials together [18][19][20][21][22][23][24]. Several groups have sought to address this limitation by developing approaches to the covalent cross-linking of PEMs by postfabrication thermal treatment [25][26][27][28][29], exposure to UV radiation [27,[30][31][32], or by treatment of preassembled PEMs with chemical cross-linking agents [33][34][35][36][37][38]. These approaches can lead to PEMs with increased stability, but thermal treatment can also alter other important film properties and these approaches are, in general, limited to the cross-linking of PEMs with appropriate combinations of mutually reactive functional groups (e.g., amine and carboxylic acid functionalities) that may or may not be present depending on the structure of the polyelectrolytes used to fabricate a film.…”
Section: Reactive Polymersmentioning
confidence: 99%